SPECTROPHOTOMETRIC DETERMINATION OF MEPHEDRONE IN A BULK FORM - Parastekar, Vaishali; Barhate, Vasant (International Journal of Current Pharmaceutical Research, 2015)
Objective: Two simple and sensitive Spectrophotometric methods are developed for estimation of Mephedrone. Methods: The first method is based on oxidation of the drug with alkaline Potassium Permanganate at room temperature (25± °c). The increase in absorbance of colored Manganate ions was measured at 610 nm. The second method is based on the oxidation of the drug with 1, 10–phenanthroline producing red colored chromogen which is measured at 510 nm. Results: All parameters affecting the developments of the color were investigated and the conditions were optimized. Under the optimum condition used, Beer's law was obeyed in the concentration range 40-160 µg/ml and 80-220 µg/ml for method A and B respectively. Molar absorptivity was found to be 4.60×102 L. mole-1 cm-1and 3.89×102 L. mole-1 cm-1 respectively. Conclusion: The proposed methods are well suited for determination of Mephedrone in bulk samples.